Politics and popular culture - Murray, Leah A. (Cambridge Scholars, 2010)
In recent years we have seen a continuation and perhaps even acceleration in the trend of popular culture having a discernible effect on politics. From The Daily Show to candidates' use of Facebook and MySpace, politics have opened up to new technologies as we come online for the next generation. Our political world has become popularized, or our popular world has become politicized in a new way, facilitated by the entertainment media and new technologies. This volume's authors attempt to ma ...